1560 Cerbe Deni̇z Savaşi - Köse, Sevilay (The Journal of Social Sciences, 2025)
Djerba Island, which had been a refuge for famous pirates since the second half of the 16th century, had an important position for the Mediterranean. Especially when Turgut Pasha, the Beylerbeyi of Tripolitania, took Djerba Island under his control, the Christian world's interest in the island increased. The Crusader troops formed to capture Djerba managed to capture the island and built a castle on the island despite the disagreement between the commanders, bad weather conditions, epidemics and deserters. Upon this news, the Ottoman navy under the command of Piyale Pasha moved towards the island of Djerba. The Ottoman fleet, which was outnumbered, defeated the Crusader fleet off the coast of Djerba. While some of the Crusaders fled, some of them took refuge in the castle of Djerba. The Crusaders were besieged by sea and land for two months. The Ottoman navy forced the Crusaders to surrender by attacking the wells in the castle. In return for the surrender of the Crusaders, their lives were spared and the island of Djerba was annexed to Tripolitania under the Ottoman Empire. This study focuses on the conquest of Djerba by the Ottoman navy, which was an important centre of refuge for Turkish pirates and the domination of the Central Mediterranean.
Keywords: Djerba -- Empire ottoman; Invasions chrétiennes -- Djerba -- 1560

Prigionia e riscatto: il capitano Gerolamo Roccabruna e la spedizione di Gerba del 1560 - Franca, Barbacovi (Studi trentini. Storia, 2020)
Keywords: Invasions chrétiennes -- Djerba -- 1560